Injectable Functional Biomaterials for Minimally Invasive Surgery. Issue 13 (2nd June 2020) - Raucci, Maria Grazia; D'Amora, Ugo; Ronca, Alfredo; Ambrosio, Luigi
Abstract: Injectable materials represent very attractive ready‐to‐use biomaterials for application in minimally invasive surgical procedures. It is shown that this approach to treat, for example, vertebral fracture, craniofacial defects, or tumor resection has significant clinical potential in the biomedical field. In the last four decades, calcium phosphate cements have been widely used as injectable materials for orthopedic surgery due to their excellent properties in terms of biocompatibility and osteoconductivity. However, few clinical studies have demonstrated certain weaknesses of these cements, which include high viscosity, long degradation time, and difficulties being manipulated. To overcome these limitations, the use of sol‐gel technology has been investigated, which has shown good results for synthesis of injectable calcium phosphate‐based materials. In the last few decades, injectable hydrogels have gained increasing attention owing to their structural similarities with the extracellular matrix, easy process conditions, and potential applications in minimally invasive surgery. However, the need to protect cells during injection leads to the development of double network injectable hydrogels that are capable of being cross‐linked in situ. This review will provide the current state of the art and recent advances in the field of injectable biomaterials for minimally invasive surgery. Abstract : This work gives an overview of the most significant advances about injectable functional biomaterials for orthopedic applications. Commercially available injectable cements, used to treat bone defects, are analyzed, followed by a review of organic–inorganic sol‐gel materials and natural and synthetic polymers/nanocomposites. Finally, an examination of injectable shape memory/self‐healing materials and double‐network hydrogels is conducted.